Plan de negocios para una cafetería, en la ciudad de Milagro - Criollo Avemañay, Genesis Lisbeth (2024)
The study responds to the growing demand for coffee consumption in the city, where there is currently a lack of establishments that offer a high-quality experience. The objective was to develop a viable business model that meets the needs of the local market, combining quality products with a welcoming atmosphere. A mixed methodology was used, with surveys of local consumers. The results revealed a significant preference for drinks such as Latte and Americano, in addition to a high appreciation for a comfortable and modern space that invites socialization; Regarding the financial analysis, backed by own capital of $20,000, it ensures the viability of the project in its first months, guaranteeing coverage of the initial operating costs and the sustainability of the business. The proposal includes the creation of a cafeteria with a minimalist and elegant design, offering high-quality products, including vegan and gluten-free options; In addition, the incorporation of technology is proposed to facilitate digital payments and the implementation of digital loyalty programs that increase customer retention; This proposal seeks to fill a gap in the Milagro market, as well as establish a new standard in the offer of cafeteria services in the region, ensuring the sustainability and success of the business in the long term. In conclusion, this business plan represents a viable and well-founded opportunity to respond to the demands of the local Milagro market, contributing to the economic growth of the city.